The Human Prothrombin-Activating Enzyme - Deggeller, K; Vreeken, J (Thrombosis and Haemostasis, 1969)
The formation and action of human prothrombin-activating enzyme is described. The study of the formation of the enzyme leads to the following conclusions :1. The enzyme is formed from factor V, factor X and phospholipid in the presence of calcium. If one of the reagents is omitted no activity develops.2. Factor V and factor X need activation by thrombin and for instance Russell Viper Venom, respectively.3. A linear relationship exists between the inverse of factor Va concentration and the inverse of enzyme concentration.4. A linear relationship exists between the inverse of factor Xa concentration and the inverse of enzyme concentration.5. A linear relationship exists between the inverse of phospholipid concentration and the inverse of enzyme concentration at small phospholipid concentration.6. A linear relationship exists between the phospholipid concentration and the inverse of enzyme concentration at high phospholipid concentration.The study of the action of the enzyme leads to the conclusion that human prothrombin is substrate and an inhibitor if present in excess.The observed phenomena are best explained by the hypothesis that factor Va and factor Xa adsorb onto the phospholipid surface. When both factors are adsorbed close together they are active as an enzyme. This activity depends on two active centers, probably one derived from factor Va and one from factor Xa.